Effect Of Additional Lemongrass (Cymbopogon Nardus L.) Powder On Antioxidant Activity And Organoleptic Quality Of Wild Cherry (Muntingia Calabura L.) Leaf Powder Mask - I Putu Widiantara; Mega Trishuta Pathiassana; Jamila A Wahab (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2021)
Muntingia calabura L., is also known as Jamaica Cherry,is one of plants in the family Muntingiaceae and a native neotropics plant from south of Mexico to Bolivia. The leave contains rich flavonoid, tannin, triterpenoid, saponin, and polyphenol as antioxidant able to reduce free radical and body healthy. This study utilized lemongrass (Cymybopogon nardus L.) as added fragrance of muntingia’s leave powder face mask. Lemongrass is also beneficial for inhibiting bacterial growth, especially Staphylococcus epidermidis brought by several vectors. The objective of this study was to understand the effect of lemongrass added to antioxidant activity of muntinga’s leave powder face mask and also the organoleptic test for this. The result showed that the treatments of lemongrass added in muntinga’s leave powder mask had significant effect antioxidant activity. In addition, the muntinga’s leave powder mask by lemongrass variation added also had significant difference on sensory quality whether on color, texture, and scent.